Alterações clínicas, nutricionais, laboratoriais e fatores indicativos de prognóstico em gatos acometidos por lipidose hepática: estudo retrospectivo (2013-2020) - Quirino, Gustavo Augusto Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Feline Hepatic Lipidosis (FHL) is characterised by the accumulation of triacylglycerol in 80% or more hepatocytes resulting in hepatic dysfunction and cholestasis. FHL basis is the permanency in a negative energy balance and a multifactor aetiology is present, thus, clinically assisted nutrition methods are required. The aim of this monography was to identify clinical, nutritional, laboratorial changes and evaluate possible prognostic factors in FHL. A retrospective study cohort method was utilised and medical records from 2013 to 2020 were assessed. Inclusion criteria was based in history of hyperoxia, or anorexia and showing, concomitantly, abdominal ultrasonographical changes such as increased hepatic echogenicity, hepatomegaly, or cholestasis. Mostly of included cases were represented by female cats, neutered, mixed breed and body condition score above or below the ideal. Mostly cats were presented as tachypnoeic, nonetheless, heart rate and rectal temperature were within normal range. None of the included cats were assisted by nasoesophageal tubes or muscle mass score system assessed and 67,5% were assisted by esophageal feeding tubes. Non survivor cats had higher blood urea nitrogen values when compared to survivors (p=0,01). Further studies about muscular catabolism, prerenal azotaemia and kidney dysfunction correlation are required to elucidate the real prognostic value found about renal function

A lipidose hepática felina (LHF) decorre do acúmulo de triglicérides em 80% ou mais dos hepáticos e culmina em disfunção hepática e colestase. Apresenta etiologia multifatorial, sendo o fator desencadeador a permanência no balanço energético negativo, sendo necessárias estratégias de nutrição assistida para seu tratamento. O objetivo deste estudo foi caracterizar padrões de alterações clínicas, nutricionais e laboratoriais em gatos acometidos por LHF e identificar possíveis fatores indicativos de prognóstico. Por metodologia de estudo retrospectivo, fichas médicas do período de 2013 a 2020 foram pesquisadas. Critérios de inclusão se basearam em histórico de hiporexia ou anorexia e demonstrando, concomitantemente, alteração de ecogenicidade hepática, hepatomegalia ou colestase pela ultrassonografia abdominal. Foi observada maior prevalência de animais fêmeas, castradas, sem raça definida, com escore de condição corporal acima ou abaixo do ideal. Gatos se apresentaram predominante taquipneicos, entretanto sem alterações de frequência cardíaca ou temperatura retal. Nenhum dos casos inclusos utilizou sonda nasoesofágica ou avaliação da escore de massa muscular, e em 67,5% houve colocação de sonda esofágica. Foi observado que gatos com concentrações séricas superiores de ureia foram à óbito quando comparado aos sobreviventes (p=0,01). São necessários novos estudos correlacionando o estado de catabolismo muscular, azotemia pré-renal e disfunção dos rins para elucidar o real valor prognóstico encontrado sobre a função renal.
Clinical, nutritional, laboratorial changes and prognostic factors in feline hepatic lipidosis: retrospective study (2013-2020)
Keywords: Feline hepatic lipidosis; Prognostic factors; Retrospective study; Lipidose hepática felina; Fatores de prognóstico; Estudo retrospectivo